Research on the Pore Evolution of Oil Shale under Different Thermal Treatment Temperatures Using NMR and FE-SEM Methods - Yan Xi; Jun Li; Wei Lian; Haifeng Fu; Yue Qi; Yudong Tian (Geofluids)
Underground in situ pyrolysis for oil shale extraction is currently significant; the evolutions in microstructure, porosity, and permeability parameters are essential factors in evaluating the productivity of oil shale after pyrolysis. With the underground oil shale reservoir core, obtained from Jimsar Sag in the Junggar Basin in China, as the research object, the samples were subjected to the treatment at different high temperatures (400°C, 500°C, 600°C, and 700°C). The NMR and FE-SEM experiments on oil shale samples were conducted; the T2 relaxation spectra, pore size distribution, and porosity and permeability variation were analyzed; and the relationships between movable fluid saturation and porosity and permeability were established, respectively. The results showed that when the thermal treatment temperature increased, the porosity and permeability of oil shale rose continuously but showed different laws. With the temperature being lower than 400°C, the porosity increased slowly, and the growth rate of porosity increased rapidly when the thermal treatment temperature was higher than 500°C. In the pyrolysis temperature range of 25°C~400°C, the growth rate of permeability was relatively slow. With the continuously enhancing temperature (500°C~600°C), the growth rate of permeability accelerated rapidly. When the temperature continued to rise (700°C), the increase of permeability began to slow down. There is a nonlinear correlation between porosity and movable fluid saturation and an approximately linear correlation between permeability and movable fluid saturation. The findings showed that 600°C was the suitable temperature for the pyrolysis of oil shale.